Cultural linguistics analysis of phraseological units with gastronomic component - E V Smirnova; L V Yliynisheva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2013)
The article is dedicated to the cultural linguistics analysis of phraseological units with gastronomic component on the example of Spanish language.